Historical tension between the holistic and dualistic view of man in the church - Herm Zandman (In die Skriflig, 2012)
Dualism has continually plagued the Church, especially from the time when Greek philosophers articulated the dualistic view of man in an excellent, scholarly way. Even when the Reformers militated against this phenomenon theologically, it still dominated life in general and Christian living in particular. This article considered the historical tension between the holistic and dualistic view of man in the church. It strove to do this by setting forth certain examples from history, showing how the Church wrestled with this tension. Furthermore, the author attempted to point out in which way the dualistic view of man was damaging to godly living, and why a holistic view of man was conducive to life under God in an ethically meaningful manner.